Progress in non-intrusive laser-based measurements of gas-phase thermoscalars and supporting modeling near catalytic interfaces. (January 2019) - Mantzaras, John
Abstract: Heterogeneous and combined hetero-/homogeneous chemical processes have attracted increased attention in many energy conversion systems, which include large-scale power generation, microreactors for portable power generation, household burners, fuel-processing technologies and automotive exhaust gas after treatment. Progress in such systems crucially depends on the development of catalysts with enhanced activity and thermal stability and on the comprehensive understanding of the fundamental processes occurring near gas–solid reacting interfaces. Recent advances in non-intrusive lased-based measurements of gas-phase thermoscalars over the catalyst boundary layer are reviewed. Such measurements, combined with theoretical analyses and numerical simulations, have fostered fundamental investigations of the catalytic and gas-phase chemical processes and their coupling at industrially-relevant operating conditions. The methodology for assessing local catalytic reaction rates and validating gas-phase reaction mechanisms under steady conditions using 1-D Raman and planar laser induced fluorescence (PLIF) of radical species, respectively, is presented first. Progress in the measurement of minor and major stable species using PLIF is outlined and the potential of this technique as a suitable method for assessing the catalytic reactivity under dynamic operating conditions is discussed. State of the art numerical modeling necessary for the interpretation of the measurements is presented in parallel with the laser-based techniques. Turbulence modeling, direct numerical simulation (DNS) and near-wall non-intrusive measurements of species concentrations and velocity have clarified aspects of the complex interplay between interphase turbulent transport and hetero-/homogeneous kinetics. Controlling parameters are the competition between the heterogeneous and homogeneous reaction pathways, diffusional imbalance of the deficient reactant, flow laminarization induced by the hot catalytic walls, and fuel leakage through the gaseous reaction zone that leads to concurrent catalytic and gas-phase combustion. Experimental needs for assessing turbulent fluctuations of catalytic reaction rates as well as for investigating intrinsic instabilities (heterogeneously or homogeneously driven) are discussed. Future directions for combining in situ surface science diagnostics with in situ non-intrusive gas-phase thermoscalar diagnostics and for advancing current numerical tools are finally proposed.